Holographic spin alignment of J/ψ meson in magnetized plasma - Yan-Qing Zhao; Xin-Li Sheng; Si-Wen Li; Defu Hou (Journal of High Energy Physics)
Abstract We study the mass spectra and spin alignment of vector meson J/ψ in a thermal magnetized background using a generalized theoretical framework based on gauge/gravity duality. Utilizing a soft wall model for the QGP background and a massive vector field for the J/ψ meson, we delve into the meson’s spectral function and spin parameters (λ θ , λ φ , λ θφ ) for different cases, assessing their response to variations in magnetic field strength, momentum, and temperature. We initially examine scenarios where a meson’s momentum aligns parallel to the magnetic field in helicity frame. Our results reveal a magnetic field-induced positive λ θ H $$ λ_{θ}^{H} $$ for low meson momentum, transitioning to negative with increased momentum. As a comparison, we also study the case of momentum perpendicular to the magnetic field and find the direction of magnetic field does not affect the qualitative behavior for the eB-dependence of λ θ H $$ λ_{θ}^{H} $$ . Moreover, we apply our model to real heavy-ion collisions for three different spin quantization directions. Further comparisons with experimental data show qualitative agreement for spin parameters λ θ and λ φ in the helicity and Collins-Soper frames.